Impacts of climate change on rice production in Chi-Moon river basin (Thai) - Buddhaboon, Chitnucha; Jintrawet, Attachai (Asia-Pacific Journal of Science and Technology, 2017)
The effects of global warming on rice production in Chi_Moon river basin covered an area of 12.0 M ha, consisting of 3.9 M ha of rice production area (3.8 M ha of rainfed main-season rice crop and 0.1 M ha of irrigated off-season rice crop). It was found that observed yields are not statistically significant different from simulated yields in both main-season and off-season rice crops. Whereas rice yields of Moon River basin would be able to increase under recent existing rice production technologies. Moreover the research indicated that there is a benefit of global warming on rainfed rice production in both Chi and Moon River Basin. Rice yield will be increased at the rate of 15.5 and 11.1 percent of the recent Chi and Moon rice yield, respectively, by the year of 2099. There will be no effect on irrigated rice production of Chi River Basin, but irrigated rice yield in Moon River Basin will be decreased by 26.3 percent during the same period.